Ensuring interpreting quality in legal and courtroom settings: Australian Language Service Providers' perspectives on their role - Ludmila Stern; Xin Liu (JoSTrans: The Journal of Specialised Translation)
In today's multicultural landscape, opportunities for interpreters to acquire professional competence through formal training in order to work in legal settings, including court, remain limited, especially in the so-called 'rare languages' of recent migrant communities. Ensuring high quality interpreting services is largely the responsibility of interpreting agencies — Language Service Providers (LSPs). This article explores the ways in which eight major Australian LSPs address the challenges of providing interpreting of a quality required in legal settings, including courts. In-depth interviews with LSPs' management reveal an uneven pattern of initiatives undertaken to address interpreter training and legal/court expertise. To mitigate risk, some LSPs, especially those employing interpreters in the Aboriginal and the so-called new & emerging languages of recent migrants, refugees and asylum seekers (Stern 2018), have undertaken capacity building and assumed a trainer's role not historically expected of them; most report imparting information that can benefit interpreters, and encouraging them to pursue professional development. While the scope of these initiatives remains limited and the pattern uneven, most LSPs have identified the necessary steps for interpreter upskilling, even if they remain aspirational.